THE COURTS WITH STAGGERED STRUCTURE OF HUACA PUCLLANA: CHARACTERIZATION AND FUNCTION OF A CEREMONIAL ARCHITECTURE LIMA - Flores Espinoza, Isabel (2012)
The courts with staggered structures constitute the architectural unit more numerous in Huaca Pucllana, in this article a detailed description is approached of these as well as a general characterization and an offer brings Lima over of his function and importance in the ritual world of the culture. Pucllana’s evidence shows peculiar characteristics as for conservation and sequences architectural that allows realizing a global offer that includes functionality and chronology. Likewise, one gives review to the existing bibliography brings over of this topic this way to sustain an offer that serves for other sites Lima and helps to characterize the monumental architecture of the Early Intermediate of the central coast.